Analytical and experimental investigations on the mechanisms of surface generation in micro grinding. (February 2020) - Setti, Dinesh; Arrabiyeh, Peter A.; Kirsch, Benjamin; Heintz, Marius; Aurich, Jan C.
Abstract: Micro grinding is an emerging technology for producing structured surfaces on hard and brittle materials. A micro pencil grinding tool (MPGT) consists of a layer of superabrasive grits, bonded to a solid cylindrical surface. Randomly distributed and geometrically undefined grits interact with the workpiece surface at random positions. These random grit positions and protrusions lead to a difference in the size of undeformed chips. This study presents an analytical method to understand the undeformed chip geometry, that considers grit kinematics. Kinematic simulation of grit trajectory paths in longitudinal direction showed a reduced number of active grits in micro grinding with an increase in speed ratio and with reduced tool dimensions. MPGTs with different diameters, grit sizes, and planar grit densities have been used to perform the experiments on a 16MnCr5 hardened steel material. The influence of maximum radial height grits on surface generation in micro grinding has been verified experimentally for up and down grinding modes. Microscopic observations of ground surfaces have shown the distinct differences between up and down grinding modes, which are similar to the surface generation in milling processes. Moreover, the formation of linear grooves with uniform depth and width unlike conventional surface grinding at lower speed ratios indicated the influence of individual grits on surface generation. Trajectory path simulation results have also shown the same observation. Graphical abstract: Image 1 Highlights: Kinematic simulations in longitudinal direction showed a reduced number of active grits in micro grinding. Maximum radial height grit influences the surface generation in micro grinding. Microscopic observations of ground surfaces have shown distinct differences between the conventional and micro grinding. A method was developed to understand the undeformed chip geometry considering grit kinematics in micro grinding.